Exact and approximate Bayesian estimates of the association of intimate partner violence and modern contraceptive use among married Filipino women. - Montes, Rosabella B.
Epidemiological data oftentimes do not satisfy the assumptions of random sampling and randomization in classical data analysis. Bayesian analysis is an alternative method. But Bayesian analysis using MCMC simulations is difficult because of the complex computing required, thus an alternative approach is presented where data prior approach is utilized. This paper is a case-control study with participants selected from married Filipino women aged 15-49 who answered the Women's Safety Module of the 2008 Philippine National Demographic and Health Survey. Logistic regression analysis using exact and approximate Bayesian approaches was used to estimate the association of intimate partner violence and modern contraceptive use among married Filipino women. Comparisons between the two approaches were based on the difference of estimates and precision of credible intervals. Significant positive association between intimate partner violence and modern contraceptive use among married Filipino women was found for both exact (OR=1.345; 90% credible interval 1.201-1.502) and approximate (OR=1.343; 90% credible interval 1.200-1.504) Bayesian approaches. The ?data prior? approximate Bayesian approach gives similar estimates with negligible differentials as the exact Bayesian approach using MCMC methods; thus it can be used as an alternative approach in producing Bayesian estimates.
Thesis (MS Public Health, Biostatistics)--University of the Philippines Manila, 2011
Keywords: Intimate partner violence